Sri Lankan clinical practice guidelines: A methodological quality assessment utilizing the AGREE II instrument. - Talagala, I. A.; Samarakoon, Y.; Senanayake, S.; Abeysena, C. (Wiley-Blackwell, 2019)
RATIONALE, AIMS, AND OBJECTIVES: Clinical practice guidelines (CPG) play a major role in patient care in Sri Lanka. This study evaluates the methodological quality of the Sri Lankan CPGs developed in 2007. METHODS: A total of 94 CPGs developed by several professional colleges in Sri Lanka in the year 2007 were evaluated by 2 independent reviewers using AGREE II instrument for their methodological quality. Item score being ≤3 points was defined as "poor quality". Each domain score was calculated according to AGREE II. A guideline was labelled as "strongly recommended" if 4 or more domains scored above 60%, "recommended for use with certain modification" if only 3 domain scores were above 60% or if 4 or more domain scores were between 30% and 60%, and "not recommended" if 4 or more domains scored less than 30%. RESULTS: Most (22.3%) guidelines were developed by the College of Pathologists. Most of the guidelines (>55%) poorly reported on all the items, except for items 1, 2, and 22 of AGREE II. Median domain scores [range] and the proportion of the guidelines with domain score of <30% were as follows: domain on scope and purpose (33.3% [2.8%-83.3%]; 42.6%), stakeholder involvement (14.9% [0.0%-61.1%]; 81.9%), rigour of development (6.1% [0.0%-49%]; 98.9%), clarity and presentation (30.5% [8.3%-61.1%]; 46.8%), and applicability (8.3% [4.2%-14.6%]; 100%). All CPGs scored 50% for "editorial independence". Reviewers reported the overall quality was poor in 86 (91.5%). Based on the definitions used in the study, of 94 CPGs, 8 (8.5%) could be recommended to be used with modifications, while 86 (91.5%) could not be recommended for clinical practice. CONCLUSIONS: The methodological quality of the CPGs was poor irrespective of the source of development. Major efforts are essential to update the CPGs according to the principles of evidence based medicine.
Indexed in MEDLINE
Keywords: Practice Guidelines as Topic; Practice Guidelines as Topic-standards; Quality Assurance, Health Care; Sri Lanka